COMPARATIVE EVALUATION OF THE EFFECT OF SMEAR LAYER REMOVAL WITH EDTA AND ND: YAG LASER ON THE APICAL MICRO LEAKAGE OF TWO EPOXY RESIN BASED ROOT CANAL SEALERS - AN INVITRO STUDY. - Subramanian, Dhanalakshmi; Kavitha, Mahendran; Gurtu, Anuraag; Balakrishnan, Bakthavatchalam; Jayaraman, Mahalakshmi (Journal of Biomedical and Pharmaceutical Research, 2019)
Aim: To compare the effect of smear layer removal with 17% EDTA and Nd:YAG laser on the apical microleakage of two resin based sealers. Materials and Methods: Sixty freshly extracted maxillary central incisor teeth with patent canals were selected. The teeth were debrided and stored in saline for 24 hours before use. The teeth were sectioned at CEJ & cleaning and shaping were done upto 50 size by step back technique. The following groups were analyzed. GROUP 1: Gutta percha (GP) + AH plus sealer without smear layer removal. GROUP 2: GP + RC seal sealer without smear layer removal. GROUP 3: GP + AH plus treated with 17% EDTA. GROUP 4: GP + RC seal treated with 17% EDTA. GROUP 5: GP + AH plus treated with Nd:YAG laser. GROUP 6: GP + RC seal treated with Nd:YAG laser. 8 samples were subjected to dye penetration study for apical microleakage & 2 samples were subjected to SEM in each group to show the effect of smear layer removal by EDTA and laser. The data were analyzed by using ANOVA and TUKEY-HSD test. Results: Groups 1 and 2 showed maximum microleakage , other groups showed lesser microleakage but there was no statistically significant difference between laser and EDTA treated Groups. Conclusion: EDTA and Nd:YAG laser can be effectively used to remove smear layer and showed less apical microleakage compared to non-treated groups. Keywords: 17% EDTA, Nd:YAG LASER , AH plus , RC sealer , Smear layer.